Taxonomic evaluation and valid publication of Sorbaria sorbifolia var. glandulifolia (Sorbarieae, Rosaceae) - Song, Jun-Ho; Hong, Suk-Pyo (Phytotaxa, 2019)
Sorbaria stellipila var. glandulosa has not previously been validly published as there was no Latin diagnosis or description and no designation of a type specimen. The combination name of Sorbaria sorbifolia f. glandulosa that was proposed by T.B. Lee was also a nomen nudum. However, recent morphological, anatomical, and numerical studies have clearly identified this as a variety of Sorbaria sorbifolia. Here, we suggest this taxon as a new variety, Sorbaria sorbifolia var. glandulifolia with full description and type designation. Moreover, nomenclatural reviews, distribution maps, and an identification key to the Sorbaria taxa (one species and two varieties) in Korea are also provided.